Impaired transport of intrinsically disordered proteins through the Sec61 and SecY translocon; implications for prion diseases. Issue 2 (4th March 2018) - Jung, Sebastian; Tatzelt, Jörg
ABSTRACT: The prion protein (PrP) is composed of two major domains of similar size. The structured C-terminal domain contains three alpha-helical regions and a short two-stranded beta-sheet, while the N-terminal domain is intrinsically disordered. The analysis of PrP mutants with deletions in the C-terminal globular domain provided the first hint that intrinsically disordered domains are inefficiently transported into the endoplasmic reticulum through the Sec61 translocon. Interestingly, C-terminally truncated PrP mutants have been linked to inherited prion disease in humans and are characterized by inefficient ER import and the formation of neurotoxic PrP conformers. In a recent study we found that the Sec61 translocon in eukaryotic cells as well as the SecY translocon in bacteria is inherently deficient in translocating intrinsically disordered proteins. Moreover, our results suggest that translocon-associated components in eukaryotic cells enable the Sec61 complex to transport secretory proteins with extended unstructured domains such as PrP and shadoo.